2019
DOI: 10.1097/rlu.0000000000002927
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of 18F-FDG PET/CT—Metabolic Parameters at Baseline and Interim Assessment in Pediatric Anaplastic Large Cell Lymphoma

Abstract: Introduction The event-free survival in pediatric anaplastic large cell lymphoma (ALCL) remains at 70% irrespective of the diverse chemotherapy regimens used. There is lack of valid prognostic factors identifying high-risk patients. We investigated the prognostic value of baseline metabolic parameters and interim response on 18F-FDG PET/CT in pediatric ALCL patients. Methods We retrospectively reviewed 40 pediatric ALCL patients with paired 18F-FDG PET/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…However, tMTV was not found to be an independent prognostic factor for PFS [2]. This contrasts with the findings of Yang et al and Mathew et al, who recently demonstrated the utility of baseline tMTV as a prognostic marker in paediatric lymphoblastic lymphoma and paediatric anaplastic large cell lymphoma, respectively [6,8]. On the other hand, Chen et al found that baseline tMTV as well as TLG are both strong independent prognostic factors for paediatric NHL, outperforming other clinical-pathological risk factors (including serum LDH and bone marrow involvement on biopsy) in predicting survival [10].…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…However, tMTV was not found to be an independent prognostic factor for PFS [2]. This contrasts with the findings of Yang et al and Mathew et al, who recently demonstrated the utility of baseline tMTV as a prognostic marker in paediatric lymphoblastic lymphoma and paediatric anaplastic large cell lymphoma, respectively [6,8]. On the other hand, Chen et al found that baseline tMTV as well as TLG are both strong independent prognostic factors for paediatric NHL, outperforming other clinical-pathological risk factors (including serum LDH and bone marrow involvement on biopsy) in predicting survival [10].…”
Section: Discussioncontrasting
confidence: 69%
“…In contrast, none of the metabolic parameters in question (SUV max , MTV, and TLG) featured as predictors for either PFS or OS, and only MTV was predictive of treatment response. Although the prognostic value of SUV max has been demonstrated in multiple studies, its reliability may be compromised by a host of factors, including but not limited to blood glucose levels, body weight, administered FDG dose (including the effects of extravasation), residual activity left in the syringe, decay of injected dose, uptake time, the presence of partial volume effects, and reconstruction parameters [2,[6][7][8][9]. In addition, SUV max is only measured by the highest image pixel in the tumor region and therefore does not show the metabolic activity of the entire tumor [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the PET scan is useful in identifying additional sites of disease in peripheral T cell lymphomas, including sALCL [5]. In addition, interim and post-treatment PET scans are useful in predicting treatment outcome [6].…”
mentioning
confidence: 99%